Analisa Proses Komunikasi Inovasi QR Code sebagai Pengembangan Objek Wisata Museum Raja Ali Haji Kota Batam - Tan, Erni; Rorong, Michael Jibrael (LPPM Universitas Putera Batam, 2022)
Batam City is the largest in the Riau Archipelago Province with many tourist destinations. One of them is theRaja Ali Haji Museum. The museum is the first museum in Batam City. The museum has 72 collections ofancient relics, so it is very interesting for local and foreign visitors to visit Batam City. But there are problemsthat visitors complain about the museum is the narratives is too short for the collection of objects, even somethat don’t have narratives, making it very difficult for visitors to know the history of the collection objects indetail. The purpose of this research is to find out the patterns, communication processes, and strategiesused by the museum in releasing its newest innovation, namely the QR Code as a substitute for detailednarratives to be conveyed to visitors and the public. Data collection techniques used interviews, observation,documentation, and literature studies. The data analysis method used is data reduction, data display, andverification with the Miles and Huberman data analysis model. The results of this study show that theinnovation of QR Code technology at the museum is very effective and visitors find it helpful to get detailedinformation on collection objects